Perspectives of healthcare stakeholders in Nigeria on the impact of COVID-19 on health services - Adeponle O. Adeoye; Yewande T. Nejo; Chinwe L. Ochu; Josephine Bayigga; Rodgers R. Ayebare; Adedayo O. Faneye; Charles O. Adewemimo; Oluwaseun Emmanuel Falayi; Adeniyi Francis Fagbamigbe; Prosper Okonkwo; Adewale Victor Opayele; Gloria Ogochukwu Nwiyi; et al. (Journal of Public Health in Africa)
Background: COVID-19 disrupted critical public health services globally. It is important to understand how the pandemic affected healthcare service delivery and utilisation in Nigeria to guide planning for future public health crises in the country.